Anthropometric Study of Head Length among Garo Tribal and Non-Tribal Adult Bangladeshi Females of Greater Mymensingh Region - Tania, Israt Jahan; Perven, Hosna Ara; Begum, Al Aharama; Nishi, Manira Khanam; Jahan, Israt (Community Based Medical Journal, 2024)
A cross-sectional, analytical type of study was conducted in the Department of Anatomy, Sir Salimullah Medical College, Dhaka, Bangladesh, from January to December of 2015, to observe the differences in head length between Garo tribal and non-tribal adult Bangladeshi females of Greater Mymensingh Region. The study subjects consist of two hundred (200) adult Bangladeshi female of greater Mymensingh districts among them, 100 were tribal (Garo) female and 100 were non-tribal female. Head length was taken the two ends of the spreading caliper were placed as one end on the glabella and the other end was fixed on the inion. Inion was identified by palpation. Conversion technique kept the caliper along a sagittal plane. Then the reading was taken from the calibrations on the caliper and was recorded in cm. The mean head length was higher in Garo tribal females than that of non-tribal females and the difference was statistically significant (p<0.0001). Our data suggests that the head length was higher in tribal female (Garo) than non-tribal female in Greater Mymensingh Region in Bangladesh. CBMJ 2024 July: vol. 13 no. 02 P: 213-217